Decreased Urine N6-methyladenosine level is closely associated with the presence of diabetic nephropathy in type 2 diabetes mellitus - Wan, Shu-jun; Hua, Qiang; Xing, Yu-jie; Cheng, Yi; Zhou, Si-min; Sun, Yue; Yao, Xin-ming; Meng, Xiang-jian; Cheng, Jin-han; Wu, Han; Zhai, Qing; Zhang, Yan; et al. (Frontiers in Endocrinology, 2022)
Background To investigate the dynamic changes of urine N6-methyladenosine (m6A) levels in patients with type 2 diabetes mellitus (T2DM) and diabetic nephropathy (DN) and evaluate the clinical significance. Methods First, the levels of urine m6A were examined and compared among 62 patients with T2DM, 70 patients with DN, and 52 age- and gender-matched normal glucose tolerant subjects (NGT) by using a MethyIFIashTM Urine m6A Quantification Kit. Subsequently, we compared the concentrations of urine m6A between different stages of DN. Moreover, statistical analysis was performed to evaluate the association of urine m6A with DN. Results The levels of m6A were significantly decreased in patients with DN [(16.10 ± 6.48) ng/ml], compared with NGT [(23.12 ± 7.52) ng/ml, P < 0.0001] and patients with T2DM [(20.39 ± 7.16) ng/ml, P < 0.0001]. Moreover, the concentrations of urine m6A were obviously reduced with the deterioration of DN. Pearson rank correlation and regression analyses revealed that m6A was significantly associated with DN (P < 0.05). The areas under the receiver operator characteristics curve (AUC) were 0.783 (95% CI, 0.699 – 0.867, P < 0.0001) for the DN and NGT groups, and 0.737 (95% CI, 0.639 – 0.835, P < 0.0001) for the macroalbuminuria and normoalbuminuria groups, and the optimal cutoff value for m6A to distinguish the DN from NGT and the macroalbuminuria from normoalbuminuria cases was 0.4687 (diagnostic sensitivity, 71%; diagnostic specificity, 76%) and 0.4494 (diagnostic sensitivity, 79%; diagnostic specificity, 66%), respectively. Conclusions The levels of urine m6A are significantly decreased in patients with DN and change with the deterioration of DN, which could serve as a prospective biomarker for the diagnosis of DN.